PEMAHAMAN AKUNTANSI, TRANSPARASI, DAN AKUNTABILITAS PADA KEPATUHAN WAJIB PAJAK BADAN - Sri Dartini, Gusti Agung Ayu; Jati, I Ketut (E-Jurnal Akuntansi, 2016)
Taxpayer Compliance is an aspect that must be considered by the government to increase tax revenues. Tax compliance is influenced by many factors, including an understanding of accounting, transparency, and accountability of taxation, as well as other factors. Those factors increase taxpayer compliance. The study was conducted in East Denpasar STO, using questionnaire method and multiple linear regression analysis. Sample taken from corporate taxpayers registered in 2009-2013 East Denpasar STO. This study examined the impact of accounting understanding, transparency, and accountability on taxpayer compliance. Based on regression analysis, it was found that the partial understanding of accounting impact on taxpayer compliance. Accountability impact on taxpayer compliance, the better accountability of tax officials will influence the level of taxpayer compliance. Transparency has no significant impact on adherence to corporate taxpayers, end results suggest that the transparency factor is not the main thing in the attitude of taxpayer compliance.
Keywords: Accounting Comprehension, Transparency, Accountability, Taxpayer Compliance